A practical boundary element analysis of slab-beam floor type. (December 2018) - Abdelhady, Ahmed U.; Rashed, Youssef F.
Abstract: This paper presents the analysis of slab-beam type floors using the boundary element method. The shear-deformable plate bending theory according to Reissner is used to model the slab, whereas the Bernnoli–Euller beam model (without losing the generality) is used to model beams. The developed formulation embeds the system of grid beams stiffness matrix into the plate bending integral equation. In other words, it can be regarded as coupling between the slab boundary elements and the beam finite elements. The resulting integral equations are solved by collocation at boundary elements and internal supporting beam nodes. The present formulation allows considering the beam real intersecting area with the slab along the beam's span. The corresponding numerical model is implemented into computer code. Applications to simple examples and real building slabs are solved then results are compared to those obtained from analytical solution, finite element method, and literature to ensure the validity of the developed formulation.